Revolutionizing Kashmir’s tandoor design: improving health, efficiency, and productivity with reduced smoke emissions - Zargar, Aquib Manzoor; Rather, Rayees Ahmad; Khan, Mohammad Mohsin (International Journal of Engineering and Technology, 2023)
In recent years, the traditional Tandoor, a key tool in bread preparation, has undergone a significant transformation driven by scientific advancements and ergonomic improvements. The conventional Tandoor historically lacked scientific refinement and ergonomic considerations, leading to problems like smoky work environments, direct hand contact with hot surfaces, and substantial heat loss. This study focuses on the innovative redesign of the Tandoor, with a focus on efficiency, health, production, and smoke reduction. The new Tandoor design features a cuboidal core with a deflector at the rear and multiple vertical channels integrated within the oven. These channels significantly increase the bread-baking surface area, with the deflector redirecting flue gases towards them to expedite baking. Bread production benefits from dual heat sources: initial heat from fuel combustion and secondary heat via altered flue gas flow, reducing the average gas temperature from 250 to 180 oC. Ergonomically, the Tandoor is designed with the outer surface at a convenient 2.5 feet above the ground to improve accessibility for the baker. A strategically positioned chimney effectively directs smoke away from nearby individuals due to its frustum shape. The Tandoor and channels are insulated with Praech, a specialized material to minimize heat loss. Detailed thermal analysis validated the design's efficiency, enhancing baker working conditions while addressing smoke-related concerns and improving production efficiency.